2018
DOI: 10.1016/j.ccell.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Pathway Drives Fusion-Negative Rhabdomyosarcoma Initiated From Non-myogenic Endothelial Progenitors

Abstract: Rhabdomyosarcoma (RMS) is a pediatric soft tissue sarcoma that histologically resembles embryonic skeletal muscle. RMS occurs throughout the body and an exclusively myogenic origin does not account for RMS occurring in sites devoid of skeletal muscle. We previously described an RMS model activating a conditional constitutively active Smoothened mutant (SmoM2) with aP2-Cre. Using genetic fate mapping, we show SmoM2 expression in Cre-expressing endothelial progenitors results in myogenic transdifferentiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 74 publications
1
76
0
Order By: Relevance
“…We identified 48 hypomethylated CpG sites (corresponding to 5 promoter‐hypomethylated genes) and only 3 hypermethylated CpG sites in mutant RAS pathway‐ compared to wild‐type RAS pathway‐FN tumors (|Δβ| ≥ 0.25 and adjusted p value <0.05) (Supporting Information Table 6). Examination of these differentially methylated genes highlighted ALDH1A3 , a gene previously reported as a potential marker for cancer stem cells in embryonal RMS . Our data showed that ALDH1A3 was promoter‐hypomethylated in RAS pathway mutant vs .…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…We identified 48 hypomethylated CpG sites (corresponding to 5 promoter‐hypomethylated genes) and only 3 hypermethylated CpG sites in mutant RAS pathway‐ compared to wild‐type RAS pathway‐FN tumors (|Δβ| ≥ 0.25 and adjusted p value <0.05) (Supporting Information Table 6). Examination of these differentially methylated genes highlighted ALDH1A3 , a gene previously reported as a potential marker for cancer stem cells in embryonal RMS . Our data showed that ALDH1A3 was promoter‐hypomethylated in RAS pathway mutant vs .…”
Section: Resultsmentioning
confidence: 51%
“…Examination of these differentially methylated genes highlighted ALDH1A3, a gene previously reported as a potential marker for cancer stem cells in embryonal RMS. 26,27 Our data showed that ALDH1A3 was promoter-hypomethylated in RAS pathway mutant vs. wildtype FN tumors (2 probes and mean p value = 0.026, representative data for CpG site cg23191950 shown in Fig. 3c).…”
Section: Dna Methylation In Ras Mutant and Wild-type Fn Rms Tumorsmentioning
confidence: 68%
“…Gene ontology analysis revealed that cell-cell adhesion, angiogenesis, and cell-matrix adhesion were the most significantly enriched GO terms among the upregulated DEGs ( Figure 4D ), and skeletal muscle contraction and muscle filament gliding were enriched among the downregulated DEGs ( Figure 4E ). Intriguingly, these GO terms have been previously shown to be among the top biological processes that shift, in an opposite manner, when non-myogenic mesenchymal cells were driven into FP-RMS (Ren et al, 2008), and in FN-RMS (Drummond et al, 2018). Importantly, GSEA analysis revealed that the gene sets altered in mesenchymal stem cells after forced expression of PAX3-FKHR(FOXO1) fusion gene to drive RMS tumorigenesis (Ren et al, 2008), were changed in an opposite direction by PROX1 silencing, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…However, PAX-FOXO1 can activate myogenic determination and MYOG expression independent of MYOD (Davicioni et al, 2006; Zhang & Wang, 2007). A recent study demonstrated that activation of the hedgehog pathway by a constitutively activated form of Smo (SmoM2) in non-myogenic endothelial progenitor cells can lead to FN-RMS development (Drummond et al, 2018). Interestingly, we detected from their data that PROX1 was among the most upregulated genes during the tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that adult heart and skeletal muscle consist of terminally differentiated cells and, therefore, avoid the risk of malignant transformation. Due to this reason, myosarcomas usually arise among children, and precursors of those can even be transdifferentiated endothelial progenitors . Small intestine cancer accounts for only 2.3% of all gastrointestinal tract cancers .…”
Section: Cancer Progression: An Anatomical Perspectivementioning
confidence: 99%